Self-efficacy and its relationship to selected sport psychological constructs in the prediction of performance in ironman triathlon - Heazlewood, I.; Burke, S. (Journal of Human Sport & Exercise, 2011)
The focus of this study was to apply this approach to an IronmanTM (3.8km swim, 180km cycle, and 42.2km run) triathlon event. The methodology utilized physiological measures (VO2max, adiposity, height, weight), history of performance and sport psychological constructs (self-efficacy, motivation, sport confidence, cognitive and somatic anxiety) to predict total performance time and individual swim, cycle and run performance times. The results, utilizing correlation, regression and path analysis indicated that performance can be predicted more accurately when variables are assessed from a variety of Human Movement domains. The correlation analysis indicated only outcome orientations (r=0.68, p<0.001) and performance orientation (r=0.70, p<0.001) were significantly correlated with triathlon performance as compared to the non-predictive value of the CSAI-2 component of somatic anxiety, the attribution variables of internal, luck and powerful others, and history of previous performance. The path model explained a significant 44% of the variance of race performance. An investigation of the mediation of efficacy on performance in the race revealed that when direct paths were drawn from self-estimations to performance, non-significant regression weights were reported for the indirect paths to predict performance.